PELATIHAN MANAJEMEN REKAM MEDIS SESUAI DENGAN STANDAR PEDOMAN PENYELENGGARAAN DAN PROSEDUR REKAM MEDIS DI PUSKESMAS KECAMATAN WERU KABUPATEN SUKOHARJO - Fahmi Hakam (Program Studi Perekam Medis & Informasi Kesehatan, 2018)
The aims of this research were to: 1) improve the quality of medical records and health workers related to health service facilities in order to be able to collect the data communicatively, 2) do the data collection correctly, 3) do the qualitative and quantitative analysis, 3) improve the management of medical record’s work unit based on the applicable standard to produce information in gaining accurate medical information. The development of medical records worker’s knowledge and competency in the local clinic was accompanied by the improvement of medical record’s management in the local clinic.Dealing with the dedication for society, the implementer team used analysis study and gave the medical record workers intervention service in the local clinic. The service was held into two stages: 1) portraying the partners’ characteristic, problems and needs of medical record workers in the local clinic, 2) giving intervention in the form of medical records management in the local clinic based on the applicable rule and standard. The interactive method was held in this service. The materials were theoretical and practical. The participants’ ability was measured by Pre-Test dan Post-Test. The implementer team monitored and evaluated the training given. The results of dedication program in “Weru” Local Clinic: 1) the employee understood more about the “UKRM” management, 2) there were many problems regarding to the duplication of medical record number and the lack of quality and completeness, 3) the implementation of this activity got positive response from the head of local clinic and the participants (employee of UKRM).Keywords: Medical record, Local clinic, Training, Competency